ACCOUNTANCY ENTANGLED BY FINANCIAL CAPITAL - Maria Smejda (Zeszyty Naukowe Wyższej Szkoły Finansów i Prawa w Bielsku-Białej)
This paper aims at presenting some contradictions that can be found in the contemporary theoretical approach to the issue of accounting. Accounting has changed the systemic perception of economic phenomena into the process related one. This may be manifested in using current value to assess fixed asset component, which results in distortions in the informative system of accounting, thus encouraging application of creative accounting. Partial contradictions demonstrated in this paper are deeply rooted in the theoretical background of accounting and they have one common foundation – seeing productive capital through the prism of financial capital. This approach results from financial capital related tendencies to search for new forms of capital returns. New accounting allows for following such tendencies on the microeconomic level. New subjective interests of accounting deepen the dichotomy between theory and practice.